2000
DOI: 10.1161/01.str.31.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Ischemic Stroke in Patients With Reduced Internal Carotid Artery Lumen Diameter Distal to Severe Symptomatic Carotid Stenosis

Abstract: on behalf of the European Carotid Surgery Trialists' Collaborative GroupBackground and Purpose-Patients with recently symptomatic severe carotid stenosis have a high risk of ischemic stroke on medical treatment. The main mechanism of stroke appears to be plaque surface thrombus formation and distal embolism. It is unclear to what extent reduction in blood flow across the stenosis, and the consequent reduction in cerebral perfusion pressure, is also important. Angiographic indices of reduced cerebral perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(87 citation statements)
references
References 54 publications
1
82
2
2
Order By: Relevance
“…The low risk of stroke in medically treated patients with NO reported by the NASCET 2 and the results published by the ECST 3 for patients with poststenotic narrowing of the ICA could lead to the clinical impression that patients with recently symptomatic NO are not at high risk of stroke, making any interventional approach to treatment unnecessary. However, an 11.1%-33% risk of ipsilateral stroke within the first year has also been reported in medically treated patients.…”
mentioning
confidence: 99%
“…The low risk of stroke in medically treated patients with NO reported by the NASCET 2 and the results published by the ECST 3 for patients with poststenotic narrowing of the ICA could lead to the clinical impression that patients with recently symptomatic NO are not at high risk of stroke, making any interventional approach to treatment unnecessary. However, an 11.1%-33% risk of ipsilateral stroke within the first year has also been reported in medically treated patients.…”
mentioning
confidence: 99%
“…However, Rothwell et al 17) discovered that patients with more severe artery stenosis had no apparent kinetic and hypoperfusion injuries after the examinations, such as positron emission tomography (PET). Unless systemic blood pressure is declined, hypoperfusion injuries may occur.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The issue of management of patients with near total ICA occlusion is highly controversial as it has been suggested that patients with reduced ICA lumen diameter distal to severe symptomatic stenosis are at low risk of ischemic stroke. [14] Currently, there are no randomized clinical trials that would address this important problem.…”
Section: Discussionmentioning
confidence: 99%